2014
DOI: 10.1136/bmjopen-2013-004203
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of HPV-16 infection in a population-based subsample of Hispanic adults

Abstract: ObjectiveThis study aimed to estimate the prevalence and correlates of seropositivity to human papillomavirus (HPV)-16 in a subsample of adults who participated in the parent study Epidemiology of Hepatitis C in the adult population of Puerto Rico (PR).SettingThe parent study was a population-based household survey aimed to estimate the seroprevalence of hepatitis C and other viral infections (hepatitis A, hepatitis B, HIV, and herpes simplex type 2) in PR (n=1654) between 2005 and 2008.ParticipantsA subsample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Our study showed a decreasing trend in HPV seropositivity with increasing age for HPV 16 and HPV 18; higher HPV 16 seroprevalence was also previously reported in younger Puerto Rican women, although no significant differences were observed across age-groups in that smaller study [12] . However, some epidemiological studies report a seropositivity peak between 30 and 44 years and then a decline through older ages [9] , [10] , [17] and others report an increasing trend of seropositivity as age increases [21] , [22] .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study showed a decreasing trend in HPV seropositivity with increasing age for HPV 16 and HPV 18; higher HPV 16 seroprevalence was also previously reported in younger Puerto Rican women, although no significant differences were observed across age-groups in that smaller study [12] . However, some epidemiological studies report a seropositivity peak between 30 and 44 years and then a decline through older ages [9] , [10] , [17] and others report an increasing trend of seropositivity as age increases [21] , [22] .…”
Section: Discussionsupporting
confidence: 78%
“…Puerto Rico is not sampled as part of NHANES, and data on HPV in this Hispanic population is limited. In a subsample of a population-based household survey conducted in 2007–2008 among individuals aged 21–64 years, 15.8% of women were seropositive to HPV 16 [12] . This study determines 2010–2013 seroprevalence to HPV 6, 11, 16 and 18 among a population-based sample of Hispanic women aged 16–64 years living in the San Juan metropolitan area (SJMA) of Puerto Rico and describes epidemiologic correlates of seropositivity.…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of HPV-related cancers [ 21 – 23 ] and a high prevalence of HPV in anogenital samples have been reported among Puerto Rican men and women [ 24 ]. The seroprevalence of HPV-16 was reported to be 11.3% in a population-based sample of adults in PR [ 25 ], which is similar to that reported in the USA (11.5%) [ 26 ]. Thus, given the high CRC mortality rates and the high incidence of HPV related morbidities in PR, the overall aim of this case-control study was to evaluate the association between CRC and HPV infection in samples from Puerto Rican Hispanics.…”
Section: Introductionsupporting
confidence: 57%
“…20,27 Several intervention strategies may be effective in increasing knowledge and uptake of screening guidelines. Two recent reviews described successful intervention strategies for Hispanic CRC screening, 28,29 including the use of bilingual navigators who are members of the targeted community, educational interventions aimed at providers, and culturally sensitive printed materials.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%